Designing and Evaluating Psychometric Properties of a Tool for Assessing Primary Elderly Health Services in Iran - Faezeh Bahador; Soad Mahfoozpour; Iravan Masoudi Asl; Shaghayegh Vahdat (ACTA MEDICA IRANICA, 2026)
Semen Accurately assessing the status of older adults and evaluating service delivery requires a standardized instrument to capture primary healthcare conditions. Therefore, this study aimed to develop and validate a tool to assess the current provision of primary preventive services for the elderly in Iran. This exploratory sequential mixed-methods study was conducted in two phases: a quantitative descriptive survey for instrument development and measurement, and a qualitative phase using content analysis to gather expert perspectives. First, a comparative analysis was performed to describe the provision of primary preventive health services for the elderly in Iran and selected countries. Expert consensus was then obtained across three Delphi rounds to design a structured questionnaire. Face and content validity (CVR and CVI) were assessed to confirm key variables and items, and internal consistency reliability was determined using Cronbach's alpha coefficient. The instrument comprised demographic characteristics and domain-specific items derived from the Delphi process. Content validity ratio (CVR) and content validity index (CVI) were established based on the evaluation of 12 academic experts for each item. Confirmatory factor analysis (CFA) was used to evaluate the relationships between latent variables and their observed indicators. The final tool consisted of 6 dimensions and 64 items. Cronbach’s alpha coefficients for the dimensions were 0.71, 0.84, 0.75, 0.76, 0.82, and 0.92, respectively, demonstrating acceptable to high internal consistency. The findings indicate that the developed tool possesses sound psychometric properties and provides a practical, standardized instrument for healthcare decision-makers to evaluate and enhance primary geriatric healthcare services.